Harm Avoidance as a possible mediator in the relationship between the 5-HTTLPR and Cognitive Anxiety in High Level Athletes - Annamaria Petito; Giovanna D'Andrea; Francesco Sessa; Francesca Fortunato; Giuseppina Iannelli; Antonello Bellomo; Maurizio Margaglione; Mario Altamura; Salvatore Iuso (Mediterranean Journal of Clinical Psychology, 2021)
Background: The identification of relationship between genes and emotional distress mediated by personality traits among high level athletes may help to implement specific clinical psychology programs. Findings suggest that 5-HTTLPR genetic polymorphisms may be associated with Harm Avoidance (HA). The present research is aimed at evaluating the relationship between HA, the serotonin transporter’s (5-HTTLPR) polymorphisms and cognitive anxiety (CA) in high level athletes during championship.